2018
DOI: 10.1371/journal.pone.0198797
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of partial or complete anterior cruciate ligament tears using patients' history elements and physical examination tests

Abstract: ObjectiveTo assess the diagnostic validity of clusters combining history elements and physical examination tests to diagnose partial or complete anterior cruciate ligament (ACL) tears.DesignProspective diagnostic study.SettingsOrthopaedic clinics (n = 2), family medicine clinics (n = 2) and community-dwelling.ParticipantsConsecutive patients with a knee complaint (n = 279) and consulting one of the participating orthopaedic surgeons (n = 3) or sport medicine physicians (n = 2).InterventionsNot applicable.Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 50 publications
3
38
1
1
Order By: Relevance
“…Similar to previous investigators, (33)(34)(35)43) we have demonstrated that a combination of clinical history and examination variables is diagnostically superior to individual elements, (24,35,39) and that immediate swelling (24,35,39) and the Lachman test result (33,35) are important diagnostic criteria for an ACL tear. Further, we have confirmed the importance of trauma (in particular sport-related) for the diagnosis of an ACL tear previously reported by Decary et al, (35) and that when considered individually, a Lachman test may be useful (LR+ between 5-10) for diagnosing, and almost conclusive (LR-between <0.1) for excluding an ACL tear when performed by clinicians with advanced orthopaedic training. (44) In contrast to past studies, (45,46) we have identified that increasing age and a family history of an ACL tear, may be important diagnostic criteria for an ACL tear.…”
Section: Building From Previous Investigationssupporting
confidence: 86%
See 2 more Smart Citations
“…Similar to previous investigators, (33)(34)(35)43) we have demonstrated that a combination of clinical history and examination variables is diagnostically superior to individual elements, (24,35,39) and that immediate swelling (24,35,39) and the Lachman test result (33,35) are important diagnostic criteria for an ACL tear. Further, we have confirmed the importance of trauma (in particular sport-related) for the diagnosis of an ACL tear previously reported by Decary et al, (35) and that when considered individually, a Lachman test may be useful (LR+ between 5-10) for diagnosing, and almost conclusive (LR-between <0.1) for excluding an ACL tear when performed by clinicians with advanced orthopaedic training. (44) In contrast to past studies, (45,46) we have identified that increasing age and a family history of an ACL tear, may be important diagnostic criteria for an ACL tear.…”
Section: Building From Previous Investigationssupporting
confidence: 86%
“…sensation at the time of injury, giving away and anterior drawer or pivot shift test result (24,35,39,43) did not factor into our findings. Reasons for this may include: previous studies smaller sample sizes; (24,34,39) differences in sample characteristics (participant age, acuteness and diversity of knee conditions); number of practitioners; practitioner characteristics (profession, experience, degree of confidence in performing and interpreting clinical tests) and; inability to assess specific variables (age, family history, 'popping' sensation or pivoting mechanism of injury) due to insufficient or lack of data availability.…”
Section: Building From Previous Investigationsmentioning
confidence: 62%
See 1 more Smart Citation
“…C Co on nc cl lu us si io on n: : Hemarthrosis aspiration improved the sensitivity of all three tests both for orthopedic consultants and emergency physicians but did not affect specificity. 1,2,12,13,14 Meta-analysis of previous studies showed that these tests have variable sensitivity and specificity especially in acute injuries. 3,4 Unreliable and inaccurate clinical examination makes clinician uncertain of the diagnosis and compel to make unnecessary, expensive MRI imaging or misdiagnose an ACL tear.…”
Section: Sensitivity and Specificity Of Anterior Cruciate Clinical Exmentioning
confidence: 99%
“…A pop at the time of injury has been shown to be one of the factors that can be used to screen for anterior cruciate ligament lesions of the knee, with high diagnostic validity for partial or complete tears. 6,17 The purpose of this study was to assess the diagnostic value of the subjective experience of a popping sensation for significant UCL injury among throwing athletes who sustained an injury causing medial elbow pain. In addition, we examined the association of a popping sensation with UCL tear severity and explored whether a pop is associated with tears at either the proximal or distal attachment site of the anterior bundle of the UCL.…”
mentioning
confidence: 99%